2021
DOI: 10.3390/microorganisms9081789
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Carbon Substrate Catabolism Pattern and Functional Metabolic Pathway for Microbiota of Limestone Caves

Abstract: Carbon utilization of bacterial communities is a key factor of the biomineralization process in limestone-rich curst areas. An efficient carbon catabolism of the microbial community is associated with the availability of carbon sources in such an ecological niche. As cave environments promote oligotrophic (carbon source stress) situations, the present study investigated the variations of different carbon substrate utilization patterns of soil and rock microbial communities between outside and inside cave envir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…This functional diversity is evidenced in the type and abundance of carbon utilized in the soil (Habig and Swanepoel, 2015;Zhao et al, 2019). Carbon source utilization at di erent growth stages of bambara groundnut Average well color development observed in carbon sources inoculated with soil samples reflects the ability of the microbes to utilize them and it is directly related to the number of species present in the soil as observed in this study and previous studies (Chen et al, 2008;Yang et al, 2013;Koner et al, 2021).…”
Section: Discussionsupporting
confidence: 75%
“…This functional diversity is evidenced in the type and abundance of carbon utilized in the soil (Habig and Swanepoel, 2015;Zhao et al, 2019). Carbon source utilization at di erent growth stages of bambara groundnut Average well color development observed in carbon sources inoculated with soil samples reflects the ability of the microbes to utilize them and it is directly related to the number of species present in the soil as observed in this study and previous studies (Chen et al, 2008;Yang et al, 2013;Koner et al, 2021).…”
Section: Discussionsupporting
confidence: 75%
“…Gaiella and Nitrospira were dominant in the surface sediments, of which Nitrospira can fix carbon and act as the primary producer in the cave ecosystem (Ortiz et al 2013). In virgin limestone caves, Cyanobacteria only existed in the soil outside the cave (Suprokash et al 2021), which further illustrated that tourism activities could change microbial community structure in the cave. There were few researches about the composition and structure of the archaeal communities in caves, but evidences showed that the Crenarchaeota accounted for 99% of the archaeal community in the bat and bird feces in primitive caves of Domica in Slovakia (Chroňáková et al 2009).…”
Section: Discussionmentioning
confidence: 95%
“…Apparently, microbial communities from these low-temperature and oligotrophic habitats are readily exploiting chemically heterogeneous organic matter. Koner et al (2021) noted that the non-ionic detergents were the fastest metabolized polymers by the rock microbiota. Utilization of carbon by bacterial communities is a key factor in the process of biomineralization in karst areas, and the efficiency of carbon catabolism is associated with the availability of different C-sources.…”
Section: Discussionmentioning
confidence: 99%
“…Taxonomic diversity of microbial communities including uncultivated fraction can be directly derived from the 16S rRNA gene sequences. Furthermore, functional information could be predicted from 16S rRNA gene amplicon-sequencing datasets by computational methods such as phylogenetic investigation of communities by the reconstruction of unobserved states (PICRUSt; Koner et al, 2021 ). By combining these approaches with community-level physiological profiling (e.g., BIOLOG ® EcoPlate™), a clearer picture of microbial diversity and metabolic potential could be drawn ( Koner et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%